Development of microfiber arrays with controlled spacing - Ke, Randal Zhiqun. (2011)
An emerging approach in Tissue Engineering (TTE) is to culture cells on a biodegradable scaffold. Existing approach generally involves in vitro culture of cell before in vivo implantation of the cell-scaffold construct. However in vitro environment has been shown to be inferior to the in vivo environment, in terms of natural healing factors and biocompatibility issues. Hence, a microfiber fabrication device has been designed and developed to produce unfused biopolymer microfiber bundles. However, the similar concept might be applicable to blood vessel tissue engineering (BVTE). For BVTE research, the scaffold material required for the in vivo cultivation should be a microfiber array with controllable spacing. Endothelial cells are expected to grow on fibers and cover the entire surface of the fibers. After polymer degradation, engineered vessel will be left. A complementary system will have to be designed and fabricated at low cost to achieve consistent parallel microfiber array control. Target microfiber spacing to achieve is 100 µm and the design of the system should not affect the original functional capabilities and performance of the device. It should also be user friendly and safe. Fiber quality should not be affected by the system and no post processing should be required to achieved the end-product . Preliminary test results show that the designed system is able to produce micro-scale fiber array control from 0 up to 357 µm. which is within the range of the target requirement. The device also fulfils all the required design specifications and also expanded the number of possible end-products achievable by the microfiber fabrication device. Furthermore, the system is modular and easy to remove, repair or replace. Finally, future work will involve fine-tuning the consistency of the motor and digitizing the controls.